ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN JARIMATIKA PADA MATA PELAJARAN MATEMATIKA DI SEKOLAH DASAR - Fitri Hamidah; Andas Nidaa’an Khofiyya; Aurellia Faradita Putri (Universitas Muhammadiyah Surabaya, 2022)
School level students (SD) have the assumption that mathematics is a complicated, boring, and monotonous subject. Learning media that is simple and easy to apply to students in mathematics can be done using the Jarimatika learning media. The purpose of this study was to analyze the effectiveness of using the learning media of Jarimatika in mathematics at the elementary school level. This study uses a type of literature review research method. The data collection technique used in this research is to use research results obtained from various journals, then analyzed further by researchers. So that it can be found the effectiveness of using the Jarimatika method in learning mathematics. Based on the results of data analysis that has been carried out by the researchers, it shows that by using the learning media of Jarimatika students can more easily calculate addition, subtraction, multiplication, and division. so that learning outcomes and student achievement have increased. This is evidenced by the results of the analysis of researchers who have an average percentage of students' classical mastery in learning mathematics of 82.6%.Â Keywords: jarimatika; mathematics; learning media